The application of metagenomic sequencing to detect and characterize emerging porcine viruses - Palinski, Rachel (Kansas State University, 2016)
Emerging viral diseases threaten the health of the US swineherd and have the potential to impact the industry. Parvoviruses are capable of infecting birds, livestock and humans, however, in swine, parvoviruses cause reproductive failure and contribute to a devastating set of diseases termed porcine circovirus associated disease (PCVAD). Here, a divergent porcine parvovirus, porcine parvovirus 7 (PPV7), distantly related to known parvovirus sequences, was identified in market pigs in the US. The PPV7 non-structural protein displayed 42.4% similarity to Eidolon helvum parvovirus 2 and 37.9% similarity to turkey parvovirus. Conserved parvovirus replicase motifs including three rolling circle replication (RCR), two NTP-binding motifs and a helicase- binding domain, were present in PPV7. Analysis by qPCR of 182 porcine samples found 16 (8.6%) positive, suggesting moderate nucleic acid prevalence in US swine. Paramyxoviruses are capable of infecting various species including cattle, pigs and humans, causing respiratory disease and importantly, can overcome species barriers causing disease. In 2013, a novel paramyxovirus sequence was described in Hong Kong, China in slaughterhouse pigs, and subsequently named porcine parainfluenza virus 1 (PPIV1). The second study identifies two complete PPIV1 genomes in US pigs originating in Oklahoma and Nebraska that display 90.0-95.3% identity to the Chinese strains. Molecular analysis by qPCR resulted in 6.1% prevalence in 279 porcine respiratory samples. Further serological analysis revealed 66.1% of 59 porcine sera samples were positive by PPIV1 F ELISA. Eleven 3-week old nursery pigs from a PPIV1 naturally infected herd were monitored for signs of infection. No clinical signs were seen in the animals, however, six pigs and the lungs of one animal tested qPCR positive by the conclusion of the study. Taken together, PPIV1 is moderately prevalent in US swine-herds. Previously known to infect avian species, canines and swine, recent reports have identified circoviruses in bats, mink, and human feces. In pigs, porcine circovirus 2 (PCV2) is essential to PCVAD, a group of diseases including reproductive failure, respiratory disease complex (PRDC), porcine dermatitis and nephropathy syndrome (PDNS) and postweaning multisystemic wasting syndrome (PMWS). Additionally, PCV2 nucleic acid has been detected in mammalian species other than swine such as cattle and mink. The final study focuses on the identification and characterization of a divergent circovirus, porcine circovirus 3, identified in aborted mummies taken from sows displaying clinical and histological signs of PDNS. Putative capsid and replicase open reading frames display 37% and 55% identity to PCV2, respectively. A retrospective study of 48 PDNS cases, PCV2 negative by immunohistochemistry (IHC), identified 45 positive and 60% of a subset, positive for PCV3 by IHC. Molecular and serological prevalence studies revealed 12.5% nucleic acid and 55% antibody prevalence in US swine samples. Collectively, these studies identify emerging porcine viruses with the potential to cause disease using metagenomic sequencing. The results of these studies will help to mitigate the risk attributed to emerging swine viruses causing disease outbreaks.
Keywords: Virology; Circovirus; Paramyxovirus; Parvovirus; Porcine Disease; Metagenomic Sequencing